The Study of Geometry in Elementary Mathematics Textbooks in Finland, Singapore, and Taiwan - Der-Ching Yang (USN Kolaka, 2020)
This study examined the differences in the presentation of geometry concepts and characteristics of geometry questions among elementary mathematics textbooks in Finland, Singapore, and Taiwan. Horizontal and vertical analysis methods were used to collect and analyze the data. A popular Mathematics textbook from a dominant publisher in each country was selected: Laskutaito from Finland, My Pals are Here! Maths from Singapore, and Kang Hsuan from Taiwan. The results indicated differences in the presentation of geometry concepts among the three textbooks series. In addition, the questions in these textbooks were determined to demonstrate different characteristics. Moreover, these findings highlight the importance of cross-national textbook comparison to enhance the understanding of differences in learning opportunities across different countries